Case Report of Pancreatic Dermoid Cyst: Can Fine Needle Aspiration Make the Diagnosis? - Lyons, Daniel A; Coberly, Emily A; Hammoud, Ghassan M; Nicholl, Michael B (JOP. Journal of the Pancreas, 2013)
Context Pancreatic dermoid cysts are rare, benign, germ cell tumors and part of the differential diagnosis for cystic neoplasms of the pancreas. Case report A 35-year-old man presented with an incidentally discovered, 2 cm cystic pancreatic neoplasm of the pancreatic tail identified on CT scan. Endoscopic ultrasound (EUS) revealed a complex, honeycomb lesion. Fine needle aspiration (FNA) yielded a sample of whitish, necrotic material containing histiocytes, benign epithelial cells, and lymphocytes. After distal pancreatectomy and splenectomy was performed, histology revealed a cyst lined by stratified squamous epithelium with benign sebaceous units consistent with a pancreatic dermoid cysts. Discussion Although axial imaging reliably detects cystic neoplasms of the pancreas, diagnostic criteria for rare lesions are lacking; therefore alternative modalities such as EUS/FNA can be utilized. This case report highlights the EUS and FNA findings associated with pancreatic dermoid cysts. Image: Stratified squamous epithelium, sebaceous units, and surrounding lymphocyte infiltration.